Functional immune diversity in reindeer reveals a high Arctic population at risk - Lukacs, Morten; Nymo, Ingebjørg H.; Madslien, Knut; Våge, Jørn; Veiberg, Vebjørn; Rolandsen, Christer Moe; Bøe, Cathrine Arnason; Sundaram, Arvind Y. M.; Grimholt, Unni (Frontiers in Ecology and Evolution, 2023)
Climate changes the geographic range of both species as well as pathogens, causing a potential increase in the vulnerability of populations or species with limited genetic diversity. With advances in high throughput sequencing (HTS) technologies, we can now define functional expressed genetic diversity of wild species at a larger scale and identify populations at risk. Previous studies have used genomic DNA to define major histocompatibility complex (MHC) class II diversity in reindeer. Varying numbers of expressed genes found in many ungulates strongly argues for using cDNA in MHC typing strategies to ensure that diversity estimates relate to functional genes. We have used available reindeer genomes to identify candidate genes and established an HTS approach to define expressed MHC class I and class II diversity. To capture a broad diversity we included samples from wild reindeer from Southern Norway, semi-domesticated reindeer from Northern Norway and reindeer from the high Artic archipelago Svalbard. Our data show a medium MHC diversity in semi-domesticated and wild Norwegian mainland reindeer, and low MHC diversity reindeer in Svalbard reindeer. The low immune diversity in Svalbard reindeer provides a potential risk if the pathogenic pressure changes in response to altered environmental conditions due to climate change, or increased human-related activity.